Association between mobile phone use and risk of rheumatoid arthritis: A large prospective cohort study - Shaoguang Ren; Peng Gao; Sitong Wei; Yang Cui; Dongqing Ye; Xinyu Fang (PLoS ONE, 2026)
Background It remains uncertain whether there is a relationship between mobile phone use and rheumatoid arthritis (RA). Research on the relationship between different mobile phone usage(MPU) behaviors and the risk of RA onset is still insufficient. Methods The UK Biobank (UKB) data were utilised to inquire into the relationship between four mobile phone use exposure variables—MPU, length of mobile phone use(LMPU), weekly usage of mobile phone for making or receiving calls(WMPU), and hands-free device/speakerphone use with mobile phones to make or receive calls(HMPU)—and new-onset RA. The relationships between MPU behaviors and the occurrence of RA in the general population were assessed using Cox regression analyses. These associations were further explored in subgroups stratified. We implemented sensitivity analyses to confirm the stability of the results. Results During a median follow-up period of 13.63 years, 6082 new cases of RA were identified among 479,966 participants. Individuals who used cell phones had a 14% elevated risk of the onset of RA (HR: 1.14, 95% CI: 1.07–1.23), with an 8% elevated risk (HR: 1.08, 95% CI: 1.02–1.15) observed among those who used a mobile phone for more than 30 minutes per week. Conclusions We aimed to investigate the association between MPU and the risk of developing RA in the general population. Results indicate that increased MPU, longer duration of use, and greater weekly mobile phone usage time may be associated with an elevated risk of developing RA.